Kinetics of BCR::ABL1 transcript levels and molecular relapse after tyrosine kinase inhibitors discontinuation in chronic myeloid leukemia patients: preliminary results from the DES-CML study - Murbach, Bruna; Duarte, Gislaine; Palma, Leonardo Carvalho; Miranda, Eliana; Duffles, Guilherme; Furlin, Graziele Pavan; Toni, Isabella; De Souza, Carmino; Binelli, Larissa; Bassan, Vitor Leonardo; de Castro, Fabiola Attie; Figueiredo-Pontes, Lorena Lobo de; et al. (Frontiers in Oncology, 2024)
Tyrosine kinase inhibitors (TKI) have revolutionized the treatment of patients with chronic myeloid leukemia. Patients who achieve sustained deep molecular response are eligible for treatment discontinuation. DES-CML is an ongoing, phase 2 multicentric discontinuation trial. Adult patients with CML in chronic phase with typical BCR::ABL1 transcripts, stable deep molecular response (MR4.5 IS) for two years, and no previous resistance were eligible. Patients underwent a phase of TKI dose de-escalation for six months before discontinuation. TKI was reintroduced at the previous dose if the patient lost major molecular response (MMR) at any time. This study aimed to assess the impact of BCR-ABL transcript kinetics during TKI de-escalation and discontinuation phases on treatment-free survival. So far, the study recruited 41 patients, and 38 patients discontinued therapy (4 were in the second discontinuation attempt). Eleven patients lost MMR, one during the de-escalation phase and ten after discontinuation. 24-month treatment-free survival was 66% (95% CI: 48-84%) in a median follow-up of 7 (1-30) months. No patient lost hematological response or had disease progression.A higher rate of molecular relapses occurred in patients with fluctuating BCR::ABL1 levels after the discontinuation phase (with loss of MR4.5, but no loss of MMR) (P=0.04, HR-4.86 (1.03-22.9) but not confirmed in the multivariate analysis. The longer duration of TKI treatment (P=0.03, HR-1.02, 95%CI -1.00-1.04) and MMR (P=0.004, HR-0.95, 95%CI -0.92-098) were independent factors of a lower relapse rate.